Russian liberalism - Robinson, Paul 1966- (NIU Series in Slavic, East European, and Eurasian Studies, 2023)
Russian Liberalism charts the development of liberal ideas and political organizations in Russia as well as the implementation of liberal reforms by the Russian and Soviet governments at various points in time. Paul Robinson's comprehensive survey covers the entire period from the late eighteenth century to the present day.Robinson demonstrates that liberalism has always lacked strong roots in the Russian population, being largely espoused by a narrow group of intellectuals whose culture it has reflected, and has tended toward a form of historical determinism that sees Russia as destined to become like the West. Many see the current political struggle between Russia and the West as being in part a conflict between the liberal West and an illiberal Russia. By explaining the historical causes of liberalism's failure in that country, Russian Liberalism offers an understanding of a significant aspect of contemporary international affairs. After Putin's February 2022 invasion of Ukraine, understanding Russian political thought is a matter of considerable importance